The presence and photoregulation of protochlorophyllide reductase in green tissues - Griffiths, W.; Kay, S.; Oliver, Richard (1984)
The enzyme protochlorophyllide (pchlide) reductase has been identified amongst the peptides, resolved by sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE), of chloroplast membranes from oat and barley plants. In support of this identification the enzymic activity associated with the enzyme has also been measured in the same preparations. A higher level of enzyme was found in plants which had been darkened prior to extraction. Based on this data, mechanisms for the light regulated diurnal variation of the reductase are discussed.